PENGARUH GAYA KOMUNIKASI GURU TERHADAP MOTIVASI BELAJAR SISWA - SUCIA, VIANESA (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2016)
Many students? failures in perceiving the information from their teacher are caused by the unsuitability of communication style between teacher and students. It means that if a teacher has appropriate style in transferring information to the students, all subjects, including citizenship, will be easily understood. Indirectly, The fun style of teacher can improve the spirit or motivation of students in learning the materials given. Learning motivation of students can be arisen from the objective or encouragement to gain the expected results. This research aimed to study the effects of communication style of the teacher of Citizenship in motivating grade 8 students of Junior High Shool 3 of Wonogiri. The reseracher took 50 students of grade 8 in Junior High School 3 of Wonogiri as the samples of the research. The data analysis applied simple linear regression analysis. Data results showed that the communication style of teacher had significant influence in motivating learning motivation of grade 8 students of Junior High school 3 of Wonogiri so that it can be concluded that the style of communication of teacher took effect significantly in motivating learning motivation of students. However, data showed that there was only 28.2% of the learning motivation coming from the teacher?s style of communication and the rest (71.8%) came from other factors such as internal and external factors (society, family).?